2011
DOI: 10.1177/1545968311405674
|View full text |Cite
|
Sign up to set email alerts
|

Dexamphetamine Improves Upper Extremity Outcome During Rehabilitation After Stroke

Abstract: In this small trial that was based on prior positive trials, significant gains in ADL and arm function suggest that the dose and timing of dexamphetamine can augment physiotherapy. Effect size calculation suggests inclusion of at least 25 patients per group in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…Recently, a pilot randomized clinical trial involving 16 patients showed that 10 mg amphetamine administered 2 days per week before physiotherapy augments the positive effects of physiotherapy on recovery of activities of daily living and arm function. 52 …”
Section: D-amphetaminementioning
confidence: 99%
“…Recently, a pilot randomized clinical trial involving 16 patients showed that 10 mg amphetamine administered 2 days per week before physiotherapy augments the positive effects of physiotherapy on recovery of activities of daily living and arm function. 52 …”
Section: D-amphetaminementioning
confidence: 99%
“…(8) No documented epileptic discharge on the electroencephalogram. (9) No pathological conditions known to be contraindications for rTMS in the guidelines suggested by Wassermann [23]. In addition, patients in whom atomoxetine use was considered to be contraindicated were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that modulation of the noradrenergic system can influence brain plasticity in human [4]. Several studies have reported that administration of amphetamine and methylphenidate improved functional outcome of stroke patients [5][6][7][8][9]. However, adverse cardiovascular events such as stroke, myocardial infarction, and sudden death and abuse potential associated with these drugs limit their use clinically in stroke rehabilitation [10,11].…”
Section: Introductionmentioning
confidence: 96%
“…Other 6 studies suggested that there was an evidence of a better relative change from baseline to follow up in motor function (WMD-6.1 points, 95% CI -10.4 to -1.9). Schuster et al 2011 have recently reported increased performance in ADL and arm function in 8 patients who were administered with 10 mg of AMPH per day [45].…”
Section: Amphetamines and Motor Rehabilitationmentioning
confidence: 99%